2018
DOI: 10.1186/s11658-018-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Essential genes of the macrophage response to Staphylococcus aureus exposure

Abstract: BackgroundAlthough significant advances have been made in understanding the mechanisms of macrophage response to Staphylococcus aureus infection, the molecular details are still elusive. Identification of the essential genes and biological processes of macrophages that are specifically changed at different durations of S. aureus exposure is of great clinical significance.MethodsWe aimed to identify the significantly changed genes and biological processes of S. aureus-exposed macrophages. We systematically anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…For example, patients with persistent SAB showed hypomethylation of the STAT1 promoter that activates the Th1 pathway, but suppresses Th17 activation. Concordantly, other studies have shown that S. aureus activates human macrophages via STAT1 ( Sun et al., 2018 ). In this scenario, greater IFNγ response would be anticipated to promote macrophage function, but reduced IL-17 would be anticipated to limit neutrophil function.…”
Section: Human Genetic Variability Correlates In S Aureus ...supporting
confidence: 67%
“…For example, patients with persistent SAB showed hypomethylation of the STAT1 promoter that activates the Th1 pathway, but suppresses Th17 activation. Concordantly, other studies have shown that S. aureus activates human macrophages via STAT1 ( Sun et al., 2018 ). In this scenario, greater IFNγ response would be anticipated to promote macrophage function, but reduced IL-17 would be anticipated to limit neutrophil function.…”
Section: Human Genetic Variability Correlates In S Aureus ...supporting
confidence: 67%
“…We identified a SNP that was associated with decreased expression of PRKCA and thus was less able to mediate the IL-17 immune response during Cryptosporidium infection. PRKCA has also been shown to be associated with numerous other infections, including infections by Staphylococcus aureus (26); with progression of sepsis (27) and toxoplasmosis (28); with Burkholderia cenocepacia infections in cystic fibrosis patients (29); and with hepatitis E virus replication (30).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers also showed that JAK2/STAT participates in immune responses in activated macrophages induced by Staphylococcus aureus and LPS [ 40 , 41 ]. Our data also implied that the JAK2-specific inhibitor, AG490 (50 μ g/mL), downregulated expression levels of proinflammatory factors TNF- α and IL-6 in macrophages treated with P. gingivalis ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%